The role of spiritually-educational work in the students’ immunity formation (Journal of Philosophy Culture and Political Science, 2018)
The article considers the problem of competences related to the willingness to implement preventionamong students of universities. Distribution of youth extremism is one of the most acute problems of modernKazakhstan.A growing number of crimes, the violence level increases, and its character become more organized.One of the key directions of the fi ght against terrorist extremist manifestations in society is their prevention. Theability of the organization of anti propaganda extremism is necessary in educational institutions.Solution to thisproblem is the introduction into curricula of higher professional education topics, highlighting the problem ofprotection from anti propaganda religious extremism. The course «Religious studies» will enable young peopleto adequately assess socially dangerous situation, connected with the manifestations of this phenomenon, to usenecessary forms of psyche control in the case of manipulating the minds of people, the victims of religiousorganizations and totalitarian direction cults.Key words: extremism, skills, young people, elective courses, educational program, ReligiousStudies, typology of the destructive religious organizations.